Memorial de formação em Medicina: de 2017 a 2023 - Costa, Pedro Rafael (Universidade Federal de São Carlos, 2023)
Report of my experience while graduating from medical school at the Federal University of São Carlos, since my arrival in the city of São Carlos in 2017 until my graduation in 2023. There where six years of learning, difficulties, dedication, skill development, discontinuance, fears and unforgettable experiences. After a brief presentation about the singularities of this medical school, I narrated the activities and events in which I participated. The elaboration of this text allowed me to revisit my training and all the feelings that arose throughout it, which guided and were responsible for building the professional that I am today.
Medical Training Memorial: from 2017 to 2023
Keywords: Narrativa reflexiva; Formação médica; CIENCIAS DA SAUDE::MEDICINA::CLINICA MEDICA